Combining lenalidomide with IL-2 family of cytokines enhances activating receptor and perforin/granzyme expression in NK cells - Alexandra Calescibetta; Robert Dalton; Nicole Fortenbery; Grace Ward; Sean Christiansen; Xianghong Chen; Pingyan Cheng; Tiffany Razabdouski; Annelise J. Glode; Nhan Tu; Thu Le Trinh; Jinghong Liu; et al. (PLoS ONE, 2026)
Background Lenalidomide is an immunomodulatory drug approved in the treatment of autoimmune disease, inflammation, and cancer. Its impact continues to grow due to its diverse spectrum of effects hampered only by toxicities and reduced efficacy. Therefore, development of strategies that enhance function while reducing drawbacks remains a prime goal. Objective and Hypothesis The mechanisms of action of lenalidomide on the activity of natural killer cells (NK cells) remains understudied yet could be critical for the development of strategies to enhance its efficacy. These cells are critical drivers of anti-tumor immune responses which are often functionally suppressed in malignancies. NK cell and T cell survival and function is driven by the IL-2 family of cytokines (IL-2 or IL-15) and work has shown that lenalidomide potentially works by increasing the secretion of IL-2 by other lymphocytes, such as CD4 + T helper cells. Thus, we hypothesized that improving NK activity with IL-2 family of cytokines could lead to enhanced lenalidomide-induced responses of these cells. Results We show that lenalidomide does not affect NK cell viability but reduces their proliferation through cell cycle arrest which could be overcome by exogenous addition of IL-2 family of cytokines. Moreover, lenalidomide induced the secretion of IL-2 on isolated NK cells although it also modulated NK receptor expression, such as NKp46, trough downregulation of PI3K/AKT pathway reduction. This was overcome by exogeneous addition of IL-2 family of cytokines increasing natural cytotoxicity, through higher perforin and granzyme expression. Mechanistically, this increased gene and protein expression occurred through the activation of STAT5 by lenalidomide which was also enhanced through the exogenous addition of IL-2 family of cytokines and modulation of IL-2R subunit changes. Conclusions These data provide a rationale for the combination of lenalidomide with IL-2 family of cytokines to enhance the effectiveness of NK cells.